Photocurable composition
By using electromagnetic spectrum radiation in the photocurable composition, the combination of (meth)acrylate, (meth)acrylate functional resin and blue fluorescent compound and benzoyl peroxide, rapid curing of the composition is achieved, The problem of insufficient curing throughput in the prior art has been solved, and the curing efficiency and speed have been significantly improved.
Patent Information
- Application Number
- CN202380043868.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-02
- Filing Date
- 2023-05-02
- Publication Date
- 2025-01-17
AI Technical Summary
The existing photocurable compositions have shortcomings in the curing transmission depth, making it difficult to achieve rapid and uniform curing under electromagnetic spectrum radiation.
Using combinations of (meth)acrylate components, (meth)acrylate functional resin components and specific blue fluorescent compounds with benzoyl peroxide as initiators, through electromagnetic spectrum radiation (such as radiation emitted by LEDs). ) realizes curing of the composition.
It significantly improves the curing depth and curing speed, ensures that the composition achieves the expected curing effect in a short time, and is suitable for medical devices and other applications.
Smart Images

Figure BDA0005160594740000061 
Figure BDA0005160594740000071 
Figure BDA0005160594740000072
Abstract
Description
Background Art Technical Field
[0001] The present invention relates to photocurable compositions having a balance of rapid cure characteristics and impressive cure through depth upon exposure to radiation in the electromagnetic spectrum.
[0002] Brief description of related technologies
[0003] Photocurable adhesive compositions are numerous and are used in large part for medical device assembly applications. Many have been commercialized where physical properties such as good tack-free cure time, good fixture time, and good tensile strength are enhanced. Cure penetration depth is notably absent from this list.
[0004] Cure-through depth refers to the ability of a dispensed photocurable adhesive sample to react such that the reacted adhesive is non-flowable in the "z" direction. Cure-through depth has been a difficult physical property to achieve in photocurable adhesives.
[0005] U.S. Patent No. 6,080,450 (Cantor) is directed to a polymerizable liquid formulation that can be cured by a combination of ultraviolet and visible light radiation to a fully cured solid deposit that exhibits a bright fluorescent response, the polymerizable liquid formulation comprising: a free radical polymerizable liquid composition; about 0.02% to 1.0%, based on the weight of the formulation, of a fluorescent agent that fluoresces at a wavelength greater than 350 nm and includes at least a portion of the visible region of the spectrum; and a catalyst system, the catalyst system comprising 0.15% to 1.0%, based on the weight of the formulation, of a phosphine oxide photoinitiator component, the phosphine oxide photoinitiator component responding to actinic radiation in a radiation band covering a range not exceeding at least 410 nm and including at least a portion of the visible spectral region and at least a portion of the ultraviolet spectral region to generate free radicals to achieve polymerization of the polymerizable liquid composition, the formulation being substantially free of non-reactive solvents.
[0006] The focus of the '450 patent is to provide a polymerizable composition curable by actinic radiation and containing a luminescent agent wherein the luminescent effect can be increased while maintaining or improving the curing characteristics of the composition.
[0007] Nonetheless, it would be desirable to improve the cure-through depth in photocurable compositions. Summary of the invention
[0008] Provided herein is a photocurable composition comprising:
[0009] (a) (meth)acrylate component;
[0010] (b) a (meth)acrylate functional resin component; and
[0011] (c) an initiator component comprising a combination of a blue fluorescent compound and a co-initiator. The fluorescent compound should absorb energy at wavelengths below about 400 nm (such as as low as 180 nm) and emit energy (or fluoresce) at wavelengths above about 400 nm (such as up to about 600 nm). Ideally, the fluorescent compound comprises 2,5-thiophenediylbis(5-tert-butyl-1,3-benzoxazole).
[0012] When exposed to a radiation source (such as a radiation source with a wavelength of 405 nm and an intensity of, for example, 100 mW / cm 2 , ideally 200mW / cm 2 When exposed to radiation from a radiation source of radiation for a period of at least about 30 seconds, the composition cures to form a cured composition exhibiting a depth of cure through a volume of the composition.
[0013] In one aspect, the present invention provides a photocurable composition comprising: (a) isobornyl (meth)acrylate in an amount of about 5 to about 50 weight %, such as about 15 to about 40 weight %, based on the total weight of the composition; (b) N,N-dimethylacrylamide in an amount of about 20 to about 30 weight %, based on the total weight of the composition; (c) a (meth)acrylate functional resin in an amount of about 15 to about 50 weight %, such as about 25 to about 35 weight %, based on the total weight of the composition; and (d) a combination of 2,5-thiophenediylbis(5-tert-butyl-1,3-benzoxazole) and benzoyl peroxide as an initiator component.
[0014] In another aspect, the present invention provides a method of curing a photocurable composition comprising the steps of applying a composition of the present invention to at least a first substrate, and exposing the composition to radiation in the electromagnetic spectrum, such as that which may be emitted from a light emitting diode ("LED"), so as to cure the composition through a depth of cure.
[0015] Surprisingly, it was found that an initiator component comprising a combination of a blue fluorescent compound and a co-initiator provides a certain depth of cure to the composition as the composition cures when exposed to radiation in the electromagnetic spectrum (such as may be emitted from an LED). More specifically, the initiator component is a combination of a fluorescent compound and a co-initiator. Ideally, the fluorescent compound comprises 2,5-thiophenediylbis(5-tert-butyl-1,3-benzoxazole). And it is noteworthy that the initiator component should be free of an added phosphine oxide photoinitiator.
[0016] The components of the composition of the present invention - including at least a urethane (meth)acrylate resin component; a (meth)acrylate component; and an initiator component - can be mixed together in any order and for a time sufficient to ensure proper dissolution or dispersion. When desired, the composition can be cured by radiation in the electromagnetic spectrum, such as UV, visible light and UV / VIS radiation, particularly 405 nm radiation, such as emitted by an LED lamp such as the LOCTITE brand CureJet. DETAILED DESCRIPTION
[0017] As described above, in one aspect, the present invention provides a photocurable composition comprising:
[0018] (a) (meth)acrylate component;
[0019] (b) a (meth)acrylate functional resin component; and
[0020] (c) an initiator component comprising a combination of a blue fluorescent compound and a co-initiator. The fluorescent compound should absorb energy at wavelengths below about 400 nm (such as as low as 180 nm) and emit energy (or fluoresce) at wavelengths above about 400 nm (such as up to about 600 nm). Ideally, the fluorescent compound comprises 2,5-thiophenediylbis(5-tert-butyl-1,3-benzoxazole). And the composition of the present invention should be free of added phosphine oxide photoinitiators.
[0021] When exposed to a radiation source (such as emitting light with a wavelength of 405 nm and an intensity of, for example, 100 mW / cm 2 , such as 200mW / cm 2 When the composition is exposed to radiation (a radiation source of radiation) for a period of at least about 30 seconds, the composition cures to form a cured composition that exhibits a depth of cure through a certain volume of the composition (also referred to as cure penetration depth or volume).
[0022] In one aspect, the present invention provides a photocurable composition comprising: (a) isobornyl (meth)acrylate in an amount of about 5 wt % to about 50 wt %, such as about 15 wt % to about 40 wt %, based on the total weight of the composition; (b) N,N-dimethylacrylamide in an amount of about 20 wt % to about 30 wt %, based on the total weight of the composition; (c) a (meth)acrylate functional resin in an amount of about 15 wt % to about 50 wt %, such as about 25 wt % to about 35 wt %, based on the total weight of the composition; and (d) a combination of 2,5-thiophenediylbis(5-tert-butyl-1,3-benzoxazole) and benzoyl peroxide as an initiator component.
[0023] In another aspect, the present invention provides a method of curing a photocurable composition comprising the steps of applying a composition of the present invention to at least a first substrate and exposing the composition to radiation in the electromagnetic spectrum, such as radiation that may be emitted from a light emitting diode ("LED"), so as to cure the composition through a depth of cure or through a volume of the composition.
[0024] It is unexpectedly found that the initiator component comprising a combination of a blue fluorescent compound and a co-initiator provides a certain depth of cure to the composition as the composition cures when exposed to radiation in the electromagnetic spectrum (such as radiation that can be emitted from an LED). More specifically, the initiator component is a combination of 2,5-thiophenediylbis(5-tert-butyl-1,3-benzoxazole) as a blue fluorescent compound and benzoyl peroxide as a co-initiator. Typically, a photocurable composition forms a skin over layer at the surface of the composition and provides little or no cure penetration depth in the absence of a secondary cure mechanism (such as moisture cure or anaerobic cure). However, here, when so exposed to radiation in the electromagnetic spectrum, the composition of the present invention exhibits a cure depth through a certain volume of the composition.
[0025] The (meth)acrylate component may include a large number of (meth)acrylate monomers, some of which are aromatic, while others are aliphatic, and still others are cycloaliphatic. Examples of such (meth)acrylate monomers include: di- or trifunctional (meth)acrylates such as polyethylene glycol di(meth)acrylate, tetrahydrofuran (meth)acrylate and tetrahydrofuran di(meth)acrylate, hydroxypropyl (meth)acrylate ("HPMA"), hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate ("TMPTMA"), diethylene glycol dimethacrylate, triethylene glycol dimethacrylate ("TRIEGMA"), benzyl methacrylate, tetraethylene glycol dimethacrylate, dipropylene glycol dimethacrylate, di-(pentylene glycol) dimethacrylate, tetraethylene glycol diacrylate (tetraethylene glycol dimethacrylate), di-(pentylene glycol) dimethacrylate, di-(di-methyl-1-prop ... diglycoldiacrylate), diglycerol tetramethacrylate, tetramethylene dimethacrylate, ethylene dimethacrylate, neopentyl glycol diacrylate, trimethylolpropane triacrylate, and bisphenol-A mono- and di(meth)acrylates (such as ethoxylated bisphenol-A (meth)acrylate (“EBIPMA”)) and bisphenol-F mono- and di(meth)acrylates (such as ethoxylated bisphenol-F (meth)acrylate).
[0026] The (meth)acrylate component should be present in an amount of about 25 wt % to about 80 wt %, such as about 55 wt % to about 65 wt %, based on the total weight of the composition.
[0027] Particularly desirable (meth)acrylate monomers include isobornyl (meth)acrylate and N,N-dimethylacrylamide, which may be used in combination.
[0028] When used in combination, (a) isobornyl (meth)acrylate should be present in an amount of about 5 wt % to about 50 wt %, such as about 15 wt % to about 40 wt %, based on the total weight of the composition; and (b) N,N-dimethylacrylamide should be present in an amount of about 20 wt % to about 30 wt %, based on the total weight of the composition.
[0029] The (meth)acrylate functional resin component includes oligomers (particularly oligomers having urethane bonds) having a number average molecular weight of about 500 to about 100,000 Mn, such as about 2,500 to about 25,000 Mn. The number average molecular weight can be measured, for example, by gel permeation chromatography.
[0030] In one aspect, the present composition comprises the (meth)acrylate functional resin component present in an amount of about 15 wt % to about 50 wt %, such as about 25 wt % to about 35 wt %, based on the total weight of the composition.
[0031] Examples of (meth)acrylate functional resins are (meth)acrylate functional urethanes, (meth)acrylate functional polyesters, and poly(isobutylene) di(meth)acrylates.
[0032] (Meth)acrylate functional urethanes (or urethane (meth)acrylate resins) suitable as the (meth)acrylate functional resin component include, for example, those disclosed in U.S. Pat. Nos. 4,018,851, 4,295,909, and 4,309,526 to Baccei and U.S. Pat. Nos. Re 33,211, 4,751,273, 4,775,732, 5,019,636, and 5,139,872 to Lapin et al.
[0033] Other examples of such (meth)acrylate functional urethanes include tetramethylene glycol urethane acrylate oligomer and propylene glycol urethane acrylate oligomer.
[0034] Still other (meth)acrylate functional urethanes are monofunctional urethane acrylate oligomers such as 4,4'-methylenebis(cyclohexyl isocyanate) terminated polypropylene end-capped with 2-hydroxyethyl acrylate and 1-dodosanol.
[0035] They also include difunctional urethane methacrylate oligomers such as toluene-2,4-diisocyanate terminated polytetramethylene glycol ether end-capped with 2-hydroxyethyl methacrylate; isophorone diisocyanate terminated polytetramethylene glycol ether end-capped with 2-hydroxyethyl methacrylate; 4,4′-methylenebis(cyclohexyl isocyanate) terminated polytetramethylene glycol ether end-capped with 2-hydroxyethyl methacrylate; and toluene-2,4-diisocyanate terminated polypropylene glycol end-capped with 2-hydroxyethyl methacrylate.
[0036] The (meth)acrylate functional resin component can be a multi- (such as di- or tri-) functional urethane acrylate oligomer, more desirably an aliphatic polyether urethane acrylate. An example of a suitable (meth)acrylate functional resin component is BOMAR BR-582-E8 (which is commercially available from Dymax Corporation, Torrington, CT), which is described as an aliphatic urethane acrylate oligomer with a polyether backbone. BOMAR BR-582-E8 is listed in the table below.
[0037] Dymax also commercially sells a series of other (meth)acrylate functional urethanes having functionalities of about 1 to about 3 and exhibiting percent elongation greater than about 50. One such (meth)acrylate functional urethane from Dymax is a trifunctional urethane acrylate oligomer, more specifically an aliphatic polyether urethane triacrylate known as BR-990.
[0038] Among the (meth)acrylate-functional urethanes are those based on polyesters or polyethers which have been reacted with aromatic, aliphatic or cycloaliphatic diisocyanates and terminated with hydroxyacrylates.
[0039] For example, difunctional urethane acrylate oligomers such as polyesters of adipic acid and diethylene glycol terminated with isophorone diisocyanate terminated with 2-hydroxyethyl acrylate (CAS 72121-94-9); polypropylene glycol terminated with toluene-2,6-diisocyanate terminated with 2-hydroxyethyl acrylate (CAS 37302-70-8); polyesters of adipic acid and diethylene glycol terminated with 4,4′-methylenebis(cyclohexyl isocyanate) terminated with 2-hydroxyethyl acrylate (CAS 69011-33-2); polyesters of adipic acid, 1,2-ethylene glycol and 1,2-propylene glycol terminated with toluene-2,4-diisocyanate terminated with 2-hydroxyethyl acrylate (CAS 69011-31-0); polyester of adipic acid, 1,2-ethylene glycol and 1,2-propylene glycol terminated with 4,4′-methylenebis(cyclohexyl isocyanate) terminated with 2-hydroxyethyl acrylate (CAS 69011-32-1); and polytetramethylene glycol ether terminated with 4,4′-methylenebis(cyclohexyl isocyanate) terminated with 2-hydroxyethyl acrylate.
[0040] The following (meth)acrylate functional urethane resins commercially available from Dymax that may be useful include BR-930D [described by the manufacturer as a polyether urethane acrylate that is flexible and weatherable, with a nominal viscosity of 7,700 at 60°C and a Tg(°C) of 95 as determined by DMA. The manufacturer claims that BR-930D has the following properties for selected applications: ideal for 3D printing resin; high heat distortion temperature; provides good toughness and impact resistance; enhanced weatherability and low skin irritation]; and BR 7432G130 [described by the manufacturer as a polyester urethane acrylate that is flexible and weatherable, with a nominal viscosity of 80,000 at 25°C and a Tg(°C) of 28 as determined by DMA]. BR-7432G130 is claimed by the manufacturer to have the following characteristics for select applications: imparts toughness; high tensile strength; improves impact resistance; adheres to polymer films; elastomeric]; and BR-3741AJ [described by the manufacturer as a polyether urethane acrylate that is flexible and weatherable with a nominal viscosity at 60°C of 25,000 and a Tg (°C) as determined by DMA of -50. The manufacturer claims that BR-3741AJ has the following characteristics for select applications: enhanced softness and flexibility; improved optical clarity; non-yellowing; improved adhesion; adheres to a wide range of substrates; exhibits hydrolytic stability; is resistant to oils and chemicals and is ideal for PSAs].
[0041] Thus, the (meth)acrylate functional urethane may be selected from a variety of materials, some of which are commercially available from Dymax and are listed in the following table along with certain notable features:
[0042]
[0043]
[0044]
[0045]
[0046]
[0047] As an example, BR-345 (meth)acrylate functionalized urethane can be prepared according to the following reaction scheme.
[0048]
[0049] Another example of a useful (meth)acrylate functionalized urethane is a block resin labeled as 4,4-(1-methylethylidene)dicyclohexanol polymer with 1,3-diisocyanatomethylbenzene and tetrahydrofuran, propylene glycol monomer (CAS No. 2243075-64-9), prepared by reacting propylene glycol monomer with a dicarboxylic acid to form a polyester diol, followed by reaction with toluene diisocyanate, and finally capping with hydroxypropyl (meth)acrylate in a sequential step.
[0050] Yet another example of a useful (meth)acrylate functional urethane is a block resin prepared from a saturated polyester diol (such as the one sold under the trade name DESMOPHEN S-1011-35) and dicyclohexylmethane-4,4'-diisocyanate (commercially available as DESMODUR W) and end-capped with 2-hydroxyethyl acrylate, the block resin being diluted with IBOA.
[0051] A resin comprising a central segment of POLYMEG 2000 (polytetramethylene ether glycol produced by polymerizing tetrahydrofuran to form a linear glycol having a backbone of tetramethylene repeating units connected by ether bonds and terminated with primary hydroxyl units) to which TDI-HBPA or IPDI-HMTD is connected by urethane bonds and terminated with TDI-HPMA or IPDI-HEMA may be used. Also, a resin prepared from a hydroxyl functionalized polyether, a polyester (commercially available as KURARAY Polyol P-2010) and TDI together with hydroxypropyl (meth)acrylate and isobornyl (meth)acrylate may be used. Likewise, a resin prepared from polyTHF (whose weight average molecular weight ("Mw") is 2,000) and TDI together with HBPA, hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate and isobornyl (meth)acrylate may be used.
[0052] In some cases, such as described in U.S. Pat. No. 10,745,590, hydrophobic (meth) acrylate functionalized urethanes may be desirable, such as those having an Mw of 35,000 to 60,000 g / mol as determined by gel permeation chromatography ("GPC"). In the case where the Mw falls within this range, the cured product may also exhibit strong cohesion and high elongation. Preferably, the hydrophobic (meth) acrylate functionalized urethane should have a functionality of the (meth) acrylate group equal to or less than 2. In the case where the functionality of the (meth) acrylate group falls within this range, the cured product may also exhibit high elongation. These hydrophobic (meth) acrylate functionalized urethanes should have a glass transition temperature value ("Tg") determined by differential scanning calorimetry ("DSC") of -60°C to 20°C.
[0053] The hydrophobic (meth) acrylate functionalized urethane can be selected from aliphatic urethane (meth) acrylates, aromatic urethane (meth) acrylates, and mixtures thereof, such as polybutadiene-based urethane (meth) acrylates, polyisobutylene-based urethane (meth) acrylates, polyisoprene-based urethane (meth) acrylates, polybutyl rubber-based urethane (meth) acrylates, and mixtures thereof. Suitable commercially available hydrophobic urethane (meth) acrylates include UT-4462 and UV36301B90 available from Nippon Gohsei; CN 9014 available from Sartomer; and SUO-H8628 available from SHIIN-A T&C.
[0054] (Meth)acrylate functionalized urethanes may also include polyurethane block copolymers having a backbone with alternating hard segments and soft segments and at least two ends. Each of the ends may be terminated with a vinyl ether, alkenyl ether or (meth)acrylate group. Such polyurethane block copolymers may be represented by the following general formula:
[0055]
[0056] wherein A is a hard segment, such as the reaction product of a polyisocyanate and an aromatic, heterocyclic or alicyclic polyol;
[0057] B is a divalent soft segment and X is a q-valent soft segment, such as wherein B and X may be divalent and multivalent groups, respectively, derived from a polyether polyol, a polyester polyol, or a hydrogenated hydrocarbon elastomer such as polybutadiene;
[0058] D is a vinyl ether or (meth)acrylate group, such as where the vinyl ether can be derived from a hydroxy-functional vinyl ether, for example 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, cyclohexanedimethanol monovinyl ether, diethylene glycol monovinyl ether, 1,6-hexanediol monovinyl ether and 3-aminopropyl vinyl ether, or the vinyl ether end groups can be derived from amino-functional vinyl ethers, in which case vinyl ether urea-terminated polyurethanes can be obtained;
[0059] p is 0-10; and
[0060] q is 2-6.
[0061] Another example of a (meth)acrylate functionalized urethane is a (meth)acrylate functionalized urethane with a polyurethane backbone, at least a portion of which includes a urethane linkage formed from isophorone diisocyanate. For example, such a (meth)acrylate functionalized urethane is made from an alkane diol (such as polypropylene glycol), isophorone diisocyanate, and a hydroxyalkyl (meth)acrylate (such as hydroxyethyl acrylate). Other examples include isophorone diisocyanate-terminated polyesters of adipic acid, diethylene glycol terminated with 2-hydroxyethyl acrylate; isophorone diisocyanate-terminated polytetramethylene glycol ether terminated with 2-hydroxyethyl methacrylate; and isophorone diisocyanate-terminated hydroxyl-terminated polybutadiene terminated with 2-hydroxyethyl acrylate.
[0062] The initiator component comprises a combination of a blue fluorescent compound and a co-initiator.
[0063] The initiator component should be present in an amount of about 0.01 wt % to about 5 wt %, such as about 0.5 wt % to about 4 wt %, based on the total weight of the composition.
[0064] The blue fluorescent compound can be selected from many known such compounds.
[0065] A blue fluorescent compound should absorb energy at wavelengths below about 400 nm, such as down to 180 nm, and emit energy (or fluoresce) at wavelengths above about 400 nm, such as up to about 600 nm.
[0066] Blue fluorescent compounds can also be considered as fluorescent whitening agents. Here, fluorescent whitening agents may include benzoxazole and its derivatives, bisbenzoxazole; bis-benzoxazolyl-stilbene; bis-benzoxazolyl-thiophene, thienylbenzoxazole and / or 2,5-thienylbis-(5-tert-butyl-1,3-benzoxazole).
[0067] Examples of commercially available fluorescent brighteners include Tinopal OB and Uvitex OB, each from BASF Corporation. These brighteners absorb UV radiation and re-emit visible blue light.
[0068] Other examples of such fluorescent compounds include:
[0069]
[0070] Additionally, other exemplary fluorescent compounds useful in the present invention include:
[0071]
[0072] However, ideally, the blue fluorescent compound should be 2,5-thiophenediylbis(5-tert-butyl-1,3-benzoxazole).
[0073] The blue fluorescent compound should be present in an amount of about 0.01 wt % to about 5 wt %, such as about 0.5 wt % to about 4 wt %, based on the total weight of the composition.
[0074] In some embodiments of the present invention, the amount of the blue fluorescent compound is 0 to 2 wt %, such as 0.05 to 1 wt %, ideally 0.05 to 0.5 wt %, based on the total weight of the photocurable composition.
[0075] The co-initiator may be selected from a variety of materials, provided that the co-initiator acts via a free radical mechanism.Ideally, the co-initiator should be benzoyl peroxide.
[0076] The co-initiator should be present in an amount of about 0.01 wt % to about 5 wt %, such as about 0.5 wt % to about 4 wt %, based on the total weight of the composition.
[0077] The present composition can also include one or more additives, such as coloring agents, such as pigments or dyes. Carbon black is a kind of such coloring agent, and can be used in an amount of about 0.0025 to about 5 weight % of the composition, such as about 0.1 to about 1 weight % of the composition. Titanium dioxide is another available coloring agent, and can be used in an amount of about 0.01 to about 3 weight % of the composition, such as about 0.1 to about 1 weight % of the composition. In addition, the color of the dye or pigment form can be used, and the color is selected from, for example, red, yellow, blue, green and purple.
[0078] In one aspect, the present invention provides a method of curing a composition of the present invention, the method comprising the steps of applying the composition to at least a first substrate, and exposing the composition to radiation in the electromagnetic spectrum, such as radiation that can be emitted from an LED source, such as those described herein.
[0079] At least one substrate may be a plastic material, which ideally should be transparent to UV light, visible light or UV / VIS light. For example, the plastic material ideally transparent to such radiation may be selected from at least one of polyvinyl chloride, polyethylene, polypropylene, polycarbonate, acrylonitrile butadiene styrene, polyethylene terephthalate and thermoplastic elastomers.
[0080] At least one of the first substrate and the second substrate to be bonded using the composition of the present invention may include the following tubing:
[0081] (i) for delivering (including draining) medical fluids, including liquids such as electrolytes, e.g. saline or blood, and gases such as oxygen;
[0082] (ii) in a form for insertion into the body, such as a catheter, for example for insertion into the vasculature, or for insertion into a tract such as the urethra;
[0083] (iii) a part of an implantable device;
[0084] (iv) for connection to a cannula (e.g., an intravenous catheter) for insertion into a subject;
[0085] (v) for connection to a medical device (such as a pump, including an insulin pump; or a hemodialysis machine);
[0086] (vi) Use as a sheath (e.g., to contain electrical wires, such as those from a medical device).
[0087] Example
[0088] The compositions of the present invention are effective when exposed to radiation in the electromagnetic spectrum (e.g., at an intensity of 100 mW / cm 2 , using an LED light source emitting light at a wavelength of 405 nm) in about 30 seconds to cure through the volume.
[0089] Initially, three commercially available photocurable products were evaluated and certain physical properties were described as a benchmark of their performance. The commercial products are: LOCTITE 3341, LOCTITE 3921 and LOCTITE 3961. As reported by the manufacturer,
[0090] LOCTITE 3341 is a clear, light yellow, light-cured, general-purpose acrylic, instant adhesive suitable for metals and stress-sensitive plastics with a high on-demand cure speed. Depth of cure is >13 mm. Tack-free time is 15 seconds. Fixture time is 8 seconds. Shore hardness: D 27. Low viscosity: 500 mPa·s. The manufacturer reports that LOCTITE 3341 contains urethane acrylate oligomer (30-60 wt %), N'N-dimethylacrylamide (10-30 wt %), acrylate esters (10-30 wt %), urethane acrylate oligomers (10-30 wt %), isobornyl acrylate (5-10 wt %), phosphine oxide (1-5 wt %), acrylate esters (1-5 wt %), and 2-hydroxyethyl acrylate (0.1-1 wt %).
[0091] LOCTITE 3921 is a light-cured, acrylic adhesive formulated to provide a flexible bond when joining stress-sensitive plastics. The product provides a cure depth of >13 mm and a fixture time of only 3 seconds. The manufacturer reports that LOCTITE 3921 contains N'N-dimethylacrylamide (10-30 wt%), an acrylate monomer (10-30 wt%), and a substituted silane (1-5 wt%).
[0092] LOCTITE 3961 contains isobornyl acrylate (30-60 wt%), N'N-dimethylacrylamide (10-30 wt%), a photoinitiator (1-3 wt%), a urethane acrylate oligomer (10-30 wt%), ethyl phenyl(2,4,6-trimethylbenzoyl)phosphonate (1-5 wt%), an acrylic acid oligomer (1-5 wt%), gamma-glycidyloxypropyltrimethoxysilane (1-5 wt%), 2-acrylic acid (1-5 wt%), 2-carboxyethyl ester (1-5 wt%), acrylates (1-5 wt%), acrylic acid (1-5 wt%), and 2-hydroxyethyl acrylate (0.1-1 wt%).
[0093] A 3 g volume of each sample was dispensed into an aluminum pan and exposed to radiation in the electromagnetic spectrum emitted from a Loctite brand 405 nm CureJet (LED radiation source) at 100 mW / cm 2 Curing under light intensity.
[0094] 0.5 wt% LUPEROXA 98 (anhydrous benzoyl peroxide) was added to each of these three commercially available products with mixing, and volumes of these samples (sample numbers 1 to 3) were dispensed into aluminum pans and exposed to radiation in the electromagnetic spectrum emitted from a Loctite brand 405 nm CureJet at 100 mW / cm 2 Curing under light intensity.
[0095] Comparing the observed depth of cure for the three commercial samples with Sample Nos. 1 to 3 based on the corresponding commercial samples with added benzoyl peroxide, it can be seen that the depth of cure is significantly increased with exposures as short as 5 seconds and certainly with 10 seconds. The observed data is recorded in Table 1 below.
[0096] Table 1
[0097]
[0098] The information reported in Table 1 shows that each of Sample Nos. 1 to 3 has improved depth of cure at as little as 5 seconds of light exposure and a very significant improvement in depth of cure after 10 seconds of light exposure compared to the corresponding base commercial product.
[0099] Next, LOCTITE 3921 was used as a control, and benzoyl peroxide was added in an amount of 0.5 wt % to prepare Sample No. 4 and 0.1 wt % to prepare Sample No. 5. Each of these three samples was dispensed into a beaker and exposed to 100 mW / cm 2 Light intensity from a Loctite brand 405 nm CureJet irradiated in the electromagnetic spectrum for 30 seconds. LOCTITE 3921 and Sample No. 4 were dispensed in 20 g portions, while Sample No. 5 was dispensed in 30 g portions. Table 2 below records the observed data.
[0100] Table 2
[0101]
[0102] The information reported in Table 2 shows that each of Sample Nos. 4-5 had improved depth of cure after 30 seconds of exposure to radiation in the electromagnetic spectrum compared to the base commercial product LOCTITE 3921. In fact, a 4 to 5 fold increase in the magnitude of the depth of cure was observed with the addition of benzoyl peroxide.
[0103] Next, three commercially available photocurable products containing fluorescent compounds were evaluated and certain physical properties were described as a benchmark for their performance. The commercial products are: LOCTITE 3041, LOCTITE 3963, and LOCTITE 3951. As reported by the manufacturer,
[0104] LOCTITE 3041 is designed for bonding cannulas into hubs, syringes and lancets.
[0105] Loctite 3963 is a low viscosity light-curing adhesive designed for applications where a fast-curing rigid adhesive is required. It is the best choice when bonding a variety of metals and plastics. Loctite 3963 maintains high adhesion to rigid substrates such as stainless steel, polycarbonate, ABS, acrylic, HDPE (when treated), PP (when treated), etc. Loctite 3963 is suitable for the assembly of disposable medical devices.
[0106] Loctite 3951 is a low viscosity light-curing adhesive designed for applications requiring a highly flexible adhesive that cures quickly. It is the best choice when bonding plasticized PVC, TPE, and thermoset rubbers. It also maintains high adhesion to rigid substrates such as polycarbonate, ABS, acrylic, HDPE (when treated), PP (when treated), etc. Loctite 3951 is suitable for the assembly of disposable medical devices.
[0107] Thus, each contains 2,5-thiophenediylbis(5-tert-butyl-1,3-benzoxazole), albeit in different concentrations. The presence of this compound in each of the three commercial products used in the assembly of disposable medical devices allows its position on the parts to be bonded to be easily checked on the parts.
[0108] Additional evaluations were performed by moving from one or more of the commercially available samples as controls to the model base formulation. The model base formulation was prepared from 35 wt % IBOA, 35 wt % DMAA, and 30 wt % BOMAR BR-582-E8. Bomar BR-582-E8 is an aliphatic polyether urethane acrylate oligomer that is claimed by manufacturer Dymax Corporation, Torrington, CT, to provide a balance of toughness and flexibility. Dymax strongly recommends this oligomer product for use in single-layer flexible coatings on metal and plastic substrates, and it is an excellent choice for impact-resistant and flex-resistant coatings, also exhibiting abrasion resistance, flexibility, gloss, hydrolytic stability, weatherability, and non-yellowing properties. Dymax reports that the oligomer product has a Tg measured by DMA of 23°C and a nominal viscosity of 60,000 cP at 50°C, and is bonded to a variety of substrates, but not to high-density polyethylene.
[0109] To the model base formulation, benzoyl peroxide was added in an amount of 0.5 wt %. To the model base formulation, benzoyl peroxide was also added in an amount of 0.5 wt %, and a fluorescent compound was also added. In two cases, the fluorescent compound was Tinopal; in the third case, the fluorescent compound was Natmar Scanning Compound SC-25 commercially available from Angstrom Technologies, Inc., Florence, KY. According to the manufacturer, SC-25 is one of Angstrom's "World Class" organic pigments and is described as an organic pigment that can be used as a dye in toluene, acetone, and alcohol. The manufacturer reports that SC-25 is a combination of 50-60 wt % of an organometallic compound and 40-50 wt % of a phosphorus aromatic compound. It has a red UV excitation color and a fluorescent emission of 615 nm. In other words, SC-25 absorbs UV radiation and re-emits visible red light.
[0110] Tinopal was used in an amount of 0.5 wt% or 1 wt%; SC-25 was used in an amount of 1 wt%. Thus, four samples were produced here, referred to as sample numbers 6-9.
[0111] Each of the four samples was dispensed into an aluminum pan in 30 g portions and exposed to 100 mW / cm 2 The light intensity was radiated from a Loctite brand 405 nm CureJet in the electromagnetic spectrum for either 10 or 30 seconds. Table 3 below records the observed data.
[0112] Sample No. 9 was divided into two data points, where Sample No. 9a was exposed to radiation in the electromagnetic spectrum for a period of 10 seconds, and Sample No. 9b was exposed to radiation in the electromagnetic spectrum for a period of 30 seconds.
[0113] Table 3
[0114]
[0115] The information recorded in Table 3 shows that when the fluorescent compound is added and the 2 When exposed to 405 nm radiation for 10 seconds or 30 seconds at a light intensity of 100 nm, the depth of cure of Samples 7 and 9b was significant compared to the corresponding controls (Samples 6, 8 and 9a).
Claims
1. A photocurable composition comprising: (a) (meth)acrylate component; (b) a (meth)acrylate functional resin component; and (c) an initiator component comprising a combination of a blue fluorescent compound and a co-initiator, wherein when exposed to a wavelength of 405 nm and an intensity of 100 mW / cm 2 When the radiation source is applied to the composition for a period of at least about 30 seconds, the composition cures to form a cured composition exhibiting a depth of cure through a volume of the composition.
2. The composition of claim 1, wherein the blue fluorescent compound should absorb energy at wavelengths below about 400 nm and emit energy at wavelengths above about 400 nm.
3. The composition of claim 1, wherein the blue fluorescent compound should absorb energy at a wavelength of about 180 nm and emit energy at a wavelength of about 600 nm. 4 . The composition of claim 1 , wherein the blue fluorescent compound comprises 2,5-thiophenediylbis(5-tert-butyl-1,3-benzoxazole).
5. The composition of claim 1, wherein the co-initiator comprises one or more peroxides.
6. The composition of claim 1, wherein the co-initiator comprises benzoyl peroxide.
7. The composition of claim 1, wherein the (meth)acrylate component comprises isobornyl (meth)acrylate and N,N-dimethylacrylamide.
8. The composition of claim 1, wherein the (meth)acrylate component is present in a range of about 25 wt% to about 80 wt%, based on the total weight of the composition.
9. The composition of claim 1, wherein the (meth)acrylate functional resin component comprises one or more of a (meth)acrylate functional urethane, a (meth)acrylate functional polyester, and a poly(isobutylene) di(meth)acrylate.
10. The composition of claim 1 wherein the (meth)acrylate functional resin component has a number average molecular weight of about 500 to about 100,000.
11. The composition of claim 1, wherein the (meth)acrylate functional resin component is present in an amount of about 15 wt% to about 50 wt%, based on the total weight of the composition.
12. The composition of claim 1, wherein the (meth)acrylate functional resin component is present in an amount of about 25 wt% to about 35 wt%, based on the total weight of the composition.
13. The composition of claim 7, wherein the isobornyl (meth)acrylate of the (meth)acrylate component is present in an amount of about 5 wt% to about 50 wt%, based on the total weight of the composition.
14. The composition of claim 7, wherein the isobornyl (meth)acrylate of the (meth)acrylate component is present in an amount of about 15 wt% to about 40 wt%, based on the total weight of the composition.
15. The composition of claim 7, wherein the N,N-dimethylacrylamide is present in an amount of about 20 wt% to about 30 wt% based on the total weight of the composition.
16. The composition of claim 1, wherein the initiator component comprises 2,5-thiophenediylbis(5-tert-butyl-1,3-benzoxazole) as a fluorescent compound and benzoyl peroxide as a co-initiator.
17. The composition of claim 1, wherein the initiator component is present in an amount of about 0.01 wt% to about 5 wt%, based on the total weight of the composition.
18. The composition of claim 1, wherein the fluorescent compound of the initiator component is present in an amount of about 0.5 wt% to about 5 wt%, based on the total weight of the composition.
19. The composition of claim 1, wherein the co-initiator of the initiator component is present in an amount of about 0.01 wt% to about 3 wt%, based on the total weight of the composition.
20. The composition of claim 1, wherein the fluorescent compound and the co-initiator of the initiator component are present in a weight ratio of about 1:1 to about 500:
1.
21. The composition of claim 1, further comprising a colorant.
22. The composition according to claim 1, comprising (a) isobornyl (meth)acrylate in an amount of about 15 wt % to about 40 wt %, based on the total weight of the composition; (b) N,N-dimethylacrylamide in an amount of about 20 wt % to about 30 wt % based on the total weight of the composition; (c) a (meth)acrylate functional resin in an amount of about 25 wt % to about 35 wt %, based on the total weight of the composition; and (d) A combination of 2,5-thiophenediylbis(5-tert-butyl-1,3-benzoxazole) and benzoyl peroxide as an initiator component.
23. The composition of claim 1, wherein the (meth)acrylate functional resin component is a polymer of 4,4-(1-methylethylene)bicyclohexanol with 1,3-diisocyanatomethylbenzene and tetrahydrofuran, propylene glycol monomers.
24. The composition of claim 1 which is free of added phosphine oxide photoinitiator.
25. A method for curing the photocurable composition according to claim 1, comprising the steps of: (a) applying a volume of the composition to at least a first substrate; and (c) exposing the composition to a wave having a wavelength of 405 nm and an intensity of 100 mW / cm 2 A radiation source is directed through a volume of the composition to cure the composition.
26. The method of claim 25, comprising bonding the first substrate to a second substrate, wherein the first substrate and the second substrate are each components of a medical device, and optionally subsequently sterilizing the bonded assembly produced by bonding the first substrate to the second substrate.
Citation Information
Patent Citations
Photo-curable adhesive composition, cured product and use thereof
US10745590B2
Curable poly(alkylene) ether polyol-based grafted resins having improved properties
US4018851A
Curable polybutadiene-based resins having improved properties
US4295909A
Unsaturated curable poly(alkylene)ether polyol-based resins having improved properties
US4309526A
Vinyl ether terminated urethane resins
US4751273A
Cited By
High-temperature-resistant polymer material composition and application thereof
CN121591961A
High temperature resistant polymerizable material composition and use thereof
CN121591961B